Experimental Study on the Influence of Snow-Melting Agents on Fiber-Reinforced Cemented Soil under Freezing-Thawing Cycles - Lina Xu; Xu Ding; Shuang Sun; Hao Gu; Lei Niu; Yang Chen (Advances in Materials Science and Engineering)
To explore the effect of snow-melting agents on the glass fiber-reinforced cemented soil under freezing-thawing cycles, three widely used snow-melting agents, including potassium acetate, magnesium chloride, and sodium sulfate, were used in this article. The effects of snow-melting agent types on the apparent damage, mass loss, and mechanical properties of fiber-reinforced cemented soil under freezing-thawing cycles were analyzed through salt freezing and unconfined compressive strength tests. The results show that the snow-melting effect of potassium acetate is the best, the snow-melting effect of magnesium chloride is the second, and the snow-melting effect of sodium sulfate is the worst. Notably, as the number of freezing-thawing cycles increases, the strength of the test block decreases to varying degrees. After the fifth freezing-thawing cycle, the strength of the block without fiber decreased by 61.30%, 70.22%, and 81.58% in clear water, potassium acetate, and magnesium chloride solution, respectively, while the test block in sodium sulfate solution lost its bearing capacity. A series of studies proved that the snow-melting agent with sodium sulfate as the main component has the most apparent erosion effect on the cemented soil, followed by magnesium chloride, and the erosion effect of potassium acetate is the weakest. The incorporation of glass fiber can effectively improve the resistance of the cemented soil under the action of various salt solution erosion and freezing-thawing coupling and has a significant effect on slowing the development of surface cracks, improving peak strength, and reducing the mass loss rate. This research will provide theoretical support for the design of subgrade and the selection of snow-melting agents in cold areas.